Long-term follow-up of colorectal cancer screening attendees identifies differences in Phascolarctobacterium spp. using 16S rRNA and metagenome sequencing - Bucher-Johannessen, Cecilie; Birkeland, Einar Elvbakken; Vinberg, Elina; Bemanian, Vahid; Hoff, Geir; Berstad, Paula; Rounge, Trine B. (Frontiers in Oncology, 2023)
Background: The microbiome has been implicated in the initiation and progression of colorectal cancer (CRC) in cross sectional studies. However, there is a lack of studies using prospectively collected samples. Methods: We analyzed 144 archived fecal samples from participants in the NORwegian Colorectal CAncer Prevention (NORCCAP) trial diagnosed with CRC or high-risk adenomas (HRA) at screening, or who remained cancer-free during 17 years of follow-up. We performed 16S rRNA sequencing of all samples, and metagenome sequencing on a subset of 47 samples. Differences in taxonomy and gene content between outcome groups were assessed for alpha and beta diversity, and differential abundance. Results: Diversity and composition analyses showed no significant differences between CRC, HRA, and healthy controls. Phascolarctobacterium succinatutens was more abundant in CRC compared to healthy controls in both the 16S and metagenome data. The abundance of Bifidobacterium and Lachnospiraceae spp. were associated with time to CRC diagnosis. Conclusion: Using a longitudinal study design, we identified three taxa as being potentially associated with CRC. These should be the focus of further studies of microbial changes occurring prior to CRC diagnosis.